Investigation of anti-diabetic potential of Diodia sarmentosa in alloxan-induced diabetic albino rats - Rosalie, Ijomone Oghogho; Ekpe, E L (Creative Pharma Assent, 2018)
Purpose: Natural remedies from medicinal plants are considered to be effective and safe alternative treatments for diabetes mellitus. Diodia sarmentosa (Rubiaceae) commonly called tropical button weed, has been used locally in the treatment of diabetes. This study demonstrates the hypoglycaemic and anti-diabetic activity of the aqueous ethanol extract and ethylacetate fractions of Diodia sarmentosa in alloxan-induced diabetic rats. Methods: 1000g of the leaves (air dried at 250C for 7days) was subjected to extraction using 80% aqueous ethanol and then fractionated with ethylacetate. This gave a percentage yield of 13.299%w/w, 28.30%w/w, and 11.62%w/w for aqueous ethanol extract, ethylacetate soluble and insoluble fraction respectively. Three doses (1000mg/kg, 500mg/kg and 250mg/kg body weight) of the three samples were administered to the test groups while Glibenclamide at dose of 2.5mg/kg body weight was administered to the control group. Comparing the activity of the plant to the standard drug, the activity of all the doses of the aqueous ethanol extract and ethylacetate insoluble fraction was comparable with that of the standard drug (Glibenclamide). Result: As regard to the dose response, the highest activity resides in the highest dose of sample administered (i.e 1000mg/kg body weight) followed by the 500mg/kg and the 250mg/kg body weight (1000mg/kg>500mg/kg>250mg/kg). The aqueous ethanol and ethylacetate soluble fractions caused a significant (p>0.05) reduction in blood glucose of the diabetic rats. Conclusion: Thus, this present study validates the medicinal potential of Diodia sarmentosa in diabetes treatment